Revisiting Atmospheric Oxidation Kinetics of Nitrogen Oxides: The Use of Low-Cost Electrochemical Sensors to Measure Reaction Kinetics - Steven M. Owen; Lachlan H. Yee; Damien T. Maher (Reactions)
The high cost of equipment is a significant entry barrier to research for smaller organisations in developing solutions to air pollution problems. Low-cost electrochemical sensors have shown sensitivity at parts-per-billion by volume (ppbV) mixing ratios but are subject to variations due to changing environmental conditions, particularly temperature. We have previously demonstrated that under isothermal/isohume conditions such as those found in kinetic studies, very stable electrochemical responses occur. In this paper, we demonstrate the utility of a low-cost IoT-based sensor system that employs four-electrode electrochemical sensors under isothermal/isohume conditions for studying the kinetics of the atmospheric oxidation of nitrogen oxides. The results suggest that reproducible results for NO and NO2 kinetics can be achieved. The method produced oxidation rates of 7.95 × 103 L2 mol−2 s−1 (±1.3%), for NO and 7.99 × 10−4 s−1 (±2.1%) for NO2. This study suggests that the oxidation kinetics of nitrogen oxides can be assessed with low-cost sensors, which can support a wide range of industrial applications, such as designing biocatalytic coatings for air pollution remediation.